Determinant of Capital Adequacy Requirements: The Role of Bank-Specific Factors in Banks Listed on The Indonesia Stock Exchange - Ricky Talumantak (Enrichment : Journal of Management, 2021)
Bank businesses have a systemic risk that could impact the economic system of a country. The regulator requires commercial banks to maintain a minimum capital requirement to absorb the exposed risk's loss. This study aimed to examine the determinants of bank capital adequacy based on bank-specific factors such as operating efficiency, liquidity, and bank size.The quantitative research approach was applied to this study by using the multiple regression method. The panel data contains commercial banks listed on the Indonesia stock exchange between the year 2015 to 2020, and a purposive sampling method was used to set up the sample. This study found that partially the operating efficiency of the banks listed in Indonesia stock exchange has a significant negative impact on capital adequacy. The bank liquidity has a significant negative impact on capital adequacy, but the bank size does not affect capital adequacy. Simultaneously, the operating efficiency, liquidity, and bank size significantly impact bank capital adequacy.